West with giraffes : a novel - Rutledge, Lynda, 1950- (Lake Union Publishing, 2021)
"'Few true friends have I known and two were giraffes...' Woodrow Wilson Nickel, age 105, feels his life ebbing away. But when he learns giraffes are going extinct, he finds himself recalling the unforgettable experience he cannot take to his grave. It's 1938. The Great Depression lingers. Hitler is threatening Europe, and world-weary Americans long for wonder. They find it in two giraffes who miraculously survive a hurricane while crossing the Atlantic. What follows is a twelve-day road trip in a custom truck to deliver Southern California's first giraffes to the San Diego Zoo. Inspired by true events, the tale weaves real-life figures with fictional ones, including the world's first female zoo director, a crusty old man with a past, a young female photographer with a secret, and assorted reprobates as spotty as the giraffes. Part adventure, part historical saga, and part coming-of-age love story, West with Giraffes explores what it means to be changed by the grace of animals, the kindness of strangers, the passing of time, and a story told before it's too late"--Publisher.